2020
DOI: 10.3390/land9090292
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Influences on LST in Two Proposed Smart Cities of India: Comparative Analysis Using Spectral Indices

Abstract: Elucidating the impact of Land Surface Temperature (LST) is an important aspect of urban studies. The impact of urbanization on LST has been widely studied to monitor the Urban Heat Island (UHI) phenomenon. However, the sensitivity of various urban factors such as urban green spaces (UGS), built-up area, and water bodies to LST is not sufficiently resolved for many urban settlements. By using remote sensing techniques, this study aimed to quantify the influence of urban factors on LST in the two traditional ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 78 publications
(62 reference statements)
2
10
0
Order By: Relevance
“…In the case investigated in this study (Babolsar and Fereydonkenar), tourism had a significant moderating effect on the LST in the tourism zones through developing green spaces that were constantly irrigated, and constructing on bare lands that were generally covered with sand. Although this study focused on the effects of the physical development of tourism instead of urban development, its results on the correlation between the land cover indices such as NDVI, MNDWI and EBBI with the LST are consistent with previous research [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the case investigated in this study (Babolsar and Fereydonkenar), tourism had a significant moderating effect on the LST in the tourism zones through developing green spaces that were constantly irrigated, and constructing on bare lands that were generally covered with sand. Although this study focused on the effects of the physical development of tourism instead of urban development, its results on the correlation between the land cover indices such as NDVI, MNDWI and EBBI with the LST are consistent with previous research [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 89%
“…This result shows that the LST has increased with increases in the area of built-up and bare lands, while increasing the area of vegetation and water bodies has reduced the LST in the study area. These particular results is in line with previous research showing the significant effect of vegetation on the LST [37,[100][101][102][103][104][105][106][107][108][109][110]. In this regard, Rahman et al [97], by modeling the spatial changes in the coastal lands and their effects on the LST characteristics, showed that physical changes due to urban development and built-up lands have a direct and significant effect on the LST, and this could pose a challenge for the residents of the studied areas in the future.…”
Section: Discussionsupporting
confidence: 89%
“…These data serve as a basis for the management of forests and agricultural crops, as well as for suitability analyses for the establishment of irrigation systems. Landsat 8 images also enable the monitoring of multiple factors affecting the urban vegetation, such as land surface temperature, urban green spaces and their proximity to water bodies and built-up area [93]. Moderate and high-resolution multispectral satellite missions are successfully used in weed detection, precise fertilization, and the determination of agricultural crop density in combination with observations using UAVs [47,94].…”
Section: Monitoring Of Vegetation Propertiesmentioning
confidence: 99%
“…The land surface temperature (LST), an indicator of the typical regional climate, can better reflect the distribution of a regional microclimate. In recent years, scholars worldwide have determinedly explored the factors associated with land surface temperature (LST), such as Ramaiah et al [1], who explored the correlation between LST and the Enhanced Built-up and Bareness Index, Modified Normalized Difference Water Index, and Soil Adjusted Vegetation Indexes, and found that both urban green spaces and water bodies could reduce LST. In another study, Hu et al [2] associated LST with three types of urban centers and explored the changing LST laws in the different urban center types.…”
Section: Introductionmentioning
confidence: 99%